Processing of Organic and Inorganic Waste Can Increase Income during The Covid-19 Pandemic - Nur Fitri Hidayanti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2022)
The study aims to find out how far the waste management process in University of Muhammadiyah Mataram. The waste in University of Muhammadiyah Mataram has not been handled as well as possible. It can be seen that there are still many landfills that are not handled properly and waste is simply dumped beside the river which is next to University of Muhammadiyah Mataram. The research used a quantitative approach and observations were made from January 2021 to March 2021. The results of the researcher' observations found that all types of waste were simply thrown away. After the researcher conducted socialization and training for all janitors at the University of Muhammadiyah Mataram, plastic wastes such as plastic bottles from beverage packaging and others have been collected and then the Bintang Sejahtera waste bank came to buy the inorganic waste, while organic waste from food scraps, especially the largest organic waste contributor came from canteen of University of Muhammadiyah Mataram, and the organic waste is used for maggot caterpillars or maggots.